Investigating the RegCM model ability in simulation ‎of summer Khorasan dust ‎ - Elham Mobarak Hassan; Ebrahim Fatahi; Abass Ranjbar Saadat Abadi; Nasim Hossein Hamzeh‎ (تحقیقات کاربردی علوم جغرافیایی)
The Great Khorasan in northeast Iran has a variety of surface structures and plains and high peaks, but due to its vicinity to the deserts of Afghanistan and Turkmenistan, it is affected by dust all the time, especially in summer. The purpose of this study was to simulate summer dust in this region by RegCM model. For this purpose, during the period 2000 to 2017, three extreme dust events were selected. The satellite image used to confirmed dust mass presence and then the synoptic structure was analyzed. Finally, the simulation results of RegCM 4.6 model were compared with the observational data including the horizontal visibility and aerosol optical depth (AOD) of Aqua satellite. The synoptic analysis showed that during the summer, low thermal pressures form in the southern Afghanistan and high pressure in the north. This structure lead to the development of north and northeast winds with speeds of 12 to 21 m / s and dust emission on the eastern border of Iran and western Afghanistan. Investigation of RegCM accuracy done by visibility, Aquas’s AOD showed that model performance in South Khorasan is better as Razavi Khorasan. The highest correlation coefficients of AOD of model and horizontal visibility were obtained at Khorasan central stations including Gonabad, Ferdows, Nahaband and Ghaen at -0.82, -0.77 and -0.44 respectively. RegCM model performed a better dust simulation in severe dust with a horizontal visibility down to less than 1000 m, high continuity and horizontal extension. Overall, the RegCM model underestimates the AOD value for the Aqua satellite algorithm.